2012
DOI: 10.5430/ijba.v3n5p64
|View full text |Cite
|
Sign up to set email alerts
|

Application of Data Envelopment Analysis to Measure the Technical Efficiency of Oil Refineries: A Case Study

Abstract: This paper is an attempt to implement the Data Envelopment Analysis (DEA) approach to measure the relative efficiency of a sample of oil refineries in Iraq over a period of two years, 2009-2010. We demonstrate that DEA is an effective tool for the Ministry of Petroleum (MOP) for monitoring and controlling the performance of oil refineries, which are growing as an important sector in Iraq. The authors followed a case study methodology where data about the inputs and outputs of refineries are gathered and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Most of the studies (Sueyoshi, 2000; Managi et al , 2004; Mekaroonreung and Johnson, 2010; Al-Najjar and Al-Jaybajy, 2012; Saglam, 2018; Hosseini and Stefaniec, 2019; Mohammed, 2020) used the production factors in the production-frontier model. These studies considered various products from petroleum refineries such as gasoline, naphtha, kerosene, fuel oil and distillate as output variables in the DEA model, and identified them as the production-frontier unit in the given set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies (Sueyoshi, 2000; Managi et al , 2004; Mekaroonreung and Johnson, 2010; Al-Najjar and Al-Jaybajy, 2012; Saglam, 2018; Hosseini and Stefaniec, 2019; Mohammed, 2020) used the production factors in the production-frontier model. These studies considered various products from petroleum refineries such as gasoline, naphtha, kerosene, fuel oil and distillate as output variables in the DEA model, and identified them as the production-frontier unit in the given set.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the unprofitable products were significantly and negatively impacted the overall efficiency. Further, Al-Najjar and Al-Jaybajy (2012) used a DEA over a sample of around 80 firms in Iraq from 2009 to 2010, and their findings revealed that the DEA could be the best tool to examine the efficiency and solve the constraints in achieving the required efficiency. Song and Zhang (2009) offered a novel support vector machine (SVM) model to measure and predict the performance of oil refineries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The performance of most refineries is measured in terms of their efficiency. Al-Najjar and Al-Jaybajy (2012) applied the concept of data envelopment analysis (DEA) to measure the efficiency of an oil refinery as the difference between best practice and observed units. In this approach, best practice was related to organisational, national and international standards.…”
Section: Performance Gapsmentioning
confidence: 99%
“…Data Envelopment Analysis (DEA) is a technique commonly used to analyze efficiency; it helps in evaluating performance and in the promotion of benchmarking in this sector. Several studies have highlighted the importance and applicability of this technique [3][4][5][6]. The main advantage of the DEA model is that it reveals inefficiencies in production unit targets, initially identified by levels of inefficiency.…”
Section: Introductionmentioning
confidence: 99%